Cross-cultural Communication and Multicultural Team Performance:: A German and American Comparison - Congden, Steven; Matveev, Alexei; Desplaces, David (Journal of Comparative International Management)

(untitled) (None, 2009)
This study builds on work by Matveev & Nelson (2004) which investigated the relationship between cross-cultural communication competence and multicultural team performance using American and Russian managers. This study examines the impact of national culture on German and American subjects. While a relationship between cross-cultural communication competence and multicultural team performance was found, it did not differ by overall national culture. Of the four dimensions of cross-cultural communication competence, only Cultural Empathy was found to be significantly different between Germans and Americans. No differences were found for the dimensions of Interpersonal Skills, Team Effectiveness, and Cultural Uncertainty.